Daniel Fabre et le conte : « Ecriture d’une différence » - Catherine Velay-Vallantin (L'Atelier du CRH)
Since the early 1970s, Daniel Fabre has emphasized the process of connection between the definition of folklore and the ethnographic practices of collecting folk tales. In doing so, he continued to work to bring to light the generic singularity of the tale, as well as the need to constitute its study as a discipline in its own right. His works and their institutional implications focus on the notions of forgetting and memory, thus showing, through a monumental and ritual itinerary, how a popular history must be able to be constructed in the form of a mythical and regionalist discourse. At the heart of the collects carried out by teachers and ethnologists, presenting this link shared between forgetfulness and memory, local folkloric narratives’ singularity emerge while changing according to the patrimonial and political relevance of the nineteenth and twentieth centuries. The storytellers do not adhere to the international or national classifications of folk tales, but they use them. Between the uses of print, especially scholarly editions, and the invention of oral performance, these storytellers have built their own popular culture.